The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/14740338.2016.1236909
|View full text |Cite
|
Sign up to set email alerts
|

Adverse safety events in patients with Chronic Kidney Disease (CKD)

Abstract: Chronic kidney disease (CKD) confers a higher risk of adverse safety events as a result of many factors including medication dosing errors and use of nephrotoxic drugs, which can cause kidney injury and renal function decline. CKD patients may also have comorbidities such as hypertension and diabetes for which they require more frequent care from different providers, and for which standard, but countervailing treatments, may put them at risk for adverse safety events. Areas covered: In addition to the well-kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 108 publications
0
10
0
Order By: Relevance
“…In the present surveillance, the incidences of overall ADRs, particularly for ADRs related to renal impairment, and serious ADRs were numerically greater in the G4 and G5 subgroups than in the G1 subgroup. Patients with renal impairment are generally more prone to AEs due to multiple factors including comorbidities and the need for polypharmacy [51]. Indeed, in RUBY, the rate of comorbidities was higher in patients with advanced renal impairment.…”
Section: Safety In Patients With Renal Impairmentmentioning
confidence: 99%
“…In the present surveillance, the incidences of overall ADRs, particularly for ADRs related to renal impairment, and serious ADRs were numerically greater in the G4 and G5 subgroups than in the G1 subgroup. Patients with renal impairment are generally more prone to AEs due to multiple factors including comorbidities and the need for polypharmacy [51]. Indeed, in RUBY, the rate of comorbidities was higher in patients with advanced renal impairment.…”
Section: Safety In Patients With Renal Impairmentmentioning
confidence: 99%
“…The complexity of this disease and its medical management predispose individuals to further complications of the cardiovascular and renal systems [3,4]. Underrecognition of impaired kidney functioning [5][6][7][8][9], presence of multiple comorbid conditions [3,5,10], and polypharmacy associated with management of comorbidities [6] often culminate in frequent hospital admissions. In a population of pre-dialysis patients with CKD in the Safe Kidney Care (SKC) Cohort Study, Ginsberg et al [4] reported that 70 % experienced at least one adverse safety incident or actionable safety finding, while over one-third had two or more.…”
mentioning
confidence: 99%
“…Acetaminophen was the most usually used pain-relieving (34% of the entire CKD cohort), although the higher doses of acetaminophen used chronically have been accompanied by analgesic nephropathy (96). To avoid toxicity, it is proposed to not exceed 3 g/day of acetaminophen (97). For moderate pain, tramadol is preferred, given its low risk of direct nephrotoxicity (98).…”
Section: Opioidsmentioning
confidence: 99%
“…For moderate pain, tramadol is preferred, given its low risk of direct nephrotoxicity (98). The use of fentanyl, alfentanil, and hydromorphone is relatively safe in dialysis patients, but doses should be adjusted to minimize the risk of respiratory depression (97). However, adjuvant medications are useful for improving pain scores, decreasing opioid doses, and treating neuropathic components of pain in dialysis patients (99).…”
Section: Opioidsmentioning
confidence: 99%